2021
DOI: 10.1177/02557614211043161
|View full text |Cite
|
Sign up to set email alerts
|

High school learners’ perceptions of value as motivation to choose music as an elective in Gauteng, South Africa

Abstract: A growing concern is the low number of learners who choose to participate in music during their high school years. Extending previous research by McPherson and O’Neill, this study explored South African high school learners’ motivation and value perceptions to continue with music as an elective in grade 10. A further objective was to understand how value perceptions vary according to grade, gender, and intention to continue with music. 180 music leaners in grades 9 and 10 completed questionnaires modeled on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
2
0
2
Order By: Relevance
“…As noted earlier, research on expectancy-value in music contexts was often conducted in North American, Oceanian, and European countries. South Africa (Parkes & Daniel, 2013; Venter, 2019) was the only African country covered, while Brazil (Hentschke, 2010) was the only South American country involved, resonating with Henrich et al’s (2010) observation that in psychological research, participants from “WEIRD” (Western, educated, industrialized, rich, and democratic) populations were most often sampled. As Henrich et al (2010) argued, “we need to be less cavalier in addressing questions of human nature on the basis of data drawn from this particularly thin, and rather unusual, slice of humanity” (p. 61).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As noted earlier, research on expectancy-value in music contexts was often conducted in North American, Oceanian, and European countries. South Africa (Parkes & Daniel, 2013; Venter, 2019) was the only African country covered, while Brazil (Hentschke, 2010) was the only South American country involved, resonating with Henrich et al’s (2010) observation that in psychological research, participants from “WEIRD” (Western, educated, industrialized, rich, and democratic) populations were most often sampled. As Henrich et al (2010) argued, “we need to be less cavalier in addressing questions of human nature on the basis of data drawn from this particularly thin, and rather unusual, slice of humanity” (p. 61).…”
Section: Discussionmentioning
confidence: 87%
“…On the one hand, studies have found that students’ value toward music mattered. Venter (2019) explored possible factors that contributed to the continuation and discontinuation of learning music among 180 ninth- and tenth-grade students. Findings indicated that students who reported higher value and competence beliefs for music than other subjects were also those who were more motivated to study music as an elective.…”
Section: Resultsmentioning
confidence: 99%
“…Semelhantemente, descobriu-se que os valores relacionados à percepção da importância de disciplinas escolares foram significativamente maiores em matemática que em música. Por fim, vale ressaltar que essas duas últimas pesquisas (TOSSAVAINEN;JUVONEN, 2015;VENTER;PANEBIANCO, 2022) encontraram um outro resultado em comum, que vai ao encontro do que foi observado também por Ghazali e McPherson (2009) -mesmo que a música não seja vista com a mesma importância de outras disciplinas, os estudantes apresentaram maior apreciação pelas aulas de música. sistemática de literatura sobre as teorias da autodeterminação e da expectativa-valor ORFEU, Florianópolis, v. 8, n. 2, p.16 -21, jun.…”
Section: Priscila Kogiaridis Ewald Caroline Caregnatounclassified
“…Os estudos também mostraram que as crianças e os adolescentes que atribuem um alto valor de utilidade para a aprendizagem musical são mais motivados a se envolverem com esse tipo de atividade (LEUNG; MCPHERSON, 2011) e que a atribuição de valor de utilidade às aulas de música é influenciada por questões familiares e culturais (GHAZALI; MCPHERSON, 2009;MCPHERSON, 2011). Por outro lado, a atribuição de um baixo valor de utilidade às aulas não resultou na desmotivação de crianças e de adolescentes, que afirmaram gostar das aulas de música mesmo diante da sua pouca utilidade para a realização de exames ou para sua profissionalização (GHAZALI; MCPHERSON, 2009;TOSSAVAINEN;JUVONEN, 2015;VENTER;PANEBIANCO, 2022).…”
Section: Priscila Kogiaridis Ewald Caroline Caregnatounclassified